Thermomechanical soil structure interaction in energy piles exhibiting reversible and irreversible interface behavior - Saeidi Rashk Olia, Arash (Kansas State University, 2023)
Energy piles are sustainable, eco-friendly, deep thermo-active foundations that combine the roles of a structural support and thermal energy carrier, thus facilitating the exchange of renewable thermal energy between the subsurface and superstructure. Although these earth-contact structures present advantageous technology based on the use of renewable thermal energy for space heating and cooling the unprecedented effects of a simultaneous action of mechanical and thermal loads require development of novel theoretical models and analyses that will ultimately enable their wider use. To this end, in this study, multiple series of mechanics based analytical solutions were derived to predict the thermomechanical interaction between the soil and energy piles. Specifically, equations that predict displacements, axial strain and stress, and interface shear stress that develops in energy piles exhibiting reversible and irreversible interface behavior were derived starting with a single energy pile embedded in the homogeneous soil profile pile exhibiting reversible interface behavior. A subsequent validation of these solutions against the results of a geotechnical centrifuge tests was successful. Additionally, upon the development of analytical solutions for a multi-layered soil profile a validation against the full scale pile test at the site comprising four different soil layers underlain by the bedrock was also successful. Furthermore, for the first time, a series of analytical solutions incorporating yielding of the soil pile interface, which is referred to as irreversible soil pile interface behavior, were derived and validated against the full-scale pile test. This series of solutions elucidated important features of the irreversible interface behavior including generation of a residual displacement, strain, axial stress and interface shear stress in a thermo-elastic energy pile, upon the inception of the interface yielding. In addition, the inception of the interface yielding also produced a change in the location of the null point. Consequently, this research contributes to filling the long-lasting gap of lack of analytical solutions that quantitatively and qualitatively describe the response of a single energy pile under thermal and combined thermomechanical load. A subsequent implementation of the analytical solutions derived in this research resulted in creation of mechanics-based load transfer diagrams that delineate a thermomechanical behavior of energy piles. Previously provided load transfer diagrams were largely speculative in that they were mostly based on the trends extracted from the experimental data. While they addressed the effects of head and tip restraints, they failed to provide quantitative assessment of displacement, strain, axial and interface shear stresses. Furthermore, the load transfer diagrams generated in this study also delineated the progression of interface yielding that culminates in the development of a constant shear stress along the pile shaft. Finally, fully coupled thermo-hydro-mechanical finite element analyses and analytical solutions were combined with statistical analyses to develop a correlation between the parameters of a finite element model and analytical solutions for isotropic and cross-anisotropic soils. Multiple linear regression models were developed and used to equalize maximum thermal axial stresses in the energy piles obtained from the finite element analyses and analytical solutions, thus leading to a correlation between the soil parameters used by analytical and finite element solutions.
Keywords: Energy piles; Analytical solutions; Thermo-mechanics; Load transfer mechanism; Soil structure interaction; Interface yielding